Behavior of fiber reinforced polymer laminates strengthening prestressed concrete beams. (2023) - Hurukadli, Parikshit; Bharti, Gaurav; Shukla, Bishnu Kant
Highlights: Determining the static response of pre-stressed concrete beams with externally bonded fiber-reinforced polymer. Three distinct GFRP laminates of two different thicknesses used to reinforce seven M 35 concrete beams. Seven M60 concrete beams reinforced using three different G F R P laminates and put to test with monotonically increasing loads. Uni-Directional Cloth, Woven Roving, Chopped Strand Mat were GFRP laminates. Deflection ductility, yield load, deflection at yield load, ultimate load, deflection at ultimate load were the main subjects of this work. Abstract: Pre-stressed concrete constructions' service life may be extended considerably by using fibre reinforced polymer (FRP) reinforcement. It is necessary to have knowledge of the real performance of the strengthened members in order to deploy the technology properly. Determining the static response of pre-stressed concrete beams with externally bonded fiber-reinforced polymer is the main objective of this work. A total of 14 beams of 3 m long, 150 mm × 250 mm cross-sectional beams were cast and put to the test in the lab. Twelve other beams had Glass Fiber Reinforced Polymer laminates added to their soffits to strengthen them, while the other two post-tensioned beams that weren't bonded functioned as reference beams. Three distinct GFRP laminates of two different thicknesses (3 mm and 5 mm) were used to reinforce seven M 35 concrete beams. The strengthened beams were put to the test with loads that increased monotonically as manual readings were collected. The remaining seven M60 concrete beams were reinforced using three different GFRP laminates of two different thicknesses 3 mm and 5 mm, and they were put to test with monotonically increasing loads while having hand readings obtained. All of the variables—concrete grade, GFRP laminate type, and GFRP laminate thickness—were assessed. Uni-Directional Cloth, Woven Roving, and Chopped Strand Mat were some of the GFRP laminates with various configurations (UDC). According to strength, stiffness, ductility, the combined action of the concrete and external reinforcement, and associated failure, all the beams that were tested under static stress underwent evaluation. Deflection ductility, yield load, deflection at yield load, ultimate load, and deflection at ultimate load were the main subjects of this work. According to static testing, pre-stressed concrete beams reinforced with externally bonded GFRP laminates have increased strength, flexural stiffness, ductility, and composite action until failure. The experiment's outcomes were discovered to be rather closely connected. Laminates were suggested for pre-stressed concrete beams with and without externally bonded GFRP in order to forecast the crucial performance factors.